Establishment of java medaka (Oryzias javanicus bleeker) as test organism for ecotoxicological studies in tropical region - Yusof, Shahrizad (2014)
The medaka fish is a group of small fish distributed in large areas in Asia. This study attempts to establish Java medaka (Oryzias javanicus) as a test organism for ecotoxicological studies in order to gain knowledge of the changes in biological processes of other organisms when exposed to pollutants. The ecology of Java medaka was investigated to understand their responses to environmental pollutants. The findings covered the distribution and localities of the fish, habitat preference or niche they occupied,relationship with other medaka species, and their spawning ground. Thirty eight localities in the coastal areas in Peninsular Malaysia were surveyed from 2008 to 2013. All localities surveyed in the west and south coast are inhabited by Java medaka in abundance but they do not occur in the east coast. In several localities, Java medaka co-exists with Indian medaka (Oryzias dancena), a phenomenon that has never been reported before. In other localities they inhabit different niche with Indian medaka, preferring areas with higher salinity while Indian medaka choose lower salinity areas. Java medaka can tolerate a wide salinity range (0.2 – 30.0 ppt), making them suitable to represent freshwater and marine environment. To support research activities using Java medaka, the laboratory culture was established. It is carried out in ambient temperature, thus, it can represent almost similar condition with the fish habitat. Their suitability for laboratory cultivation, ease of maintenance, regular spawning, short embryonic period and generation time make Java medaka a convenient test organism. The laboratory culture established in this study further ensures that the test fish is of high quality, free from parasites and diseases. The sensitivity of different life stages of Java medaka to environmental pollutants was tested. All life stages of the fish has been utilised and they have shown particular sensitivity. The embryos were sensitive to low concentrations (0.01 – 0.05 ppm) of heavy metals (Cd, Hg, Pb, Cu and Zn) in terms of developmental impairments. The most significant impairment was embryonic death which was metal dependent where the rank of metal severity is as follows: Cd (47.0- 100%) > Hg (22.0 - 64.0%) > Pb (10.0 - 55.0%) > Zn (6.0 - 40.0%) >Cu (4.0- 38.0%). In exposure to glyphosate-based herbicide, embryonic death was found to be directly proportional to the exposure concentrations. Other developmental endpoints in embryos exposed to the pollutants tested include embryotoxicity and teratogenicity. The developmental stages of Java medaka constitute simple and effective models for evaluating pollutant impact. The induction of micronucleus formation and nuclear abnormalities when the adult fish were exposed to very low levels of Cd and Hg (1.0 and 10.0 ppb) and the induction of only nuclear abnormalities in exposure to higher concentrations of Cu and Zn (10.0 and 100.0 ppb) showed the difference in their genotoxic responses towards different metals. Utilizing Java medaka in testing will closely reflect the impacts of toxic pollutants on the environment particularly for the tropical region. As the fish is new to many local researchers, the findings of this study provide the much needed information. Future researches can utilise the fish in various fields of scientific investigation.